Simple and Efficient Programming with C# - Skills to Build Applications with Visual Studio and .NET - Sarcar, Vaskaran (Apress, an imprint of Springer Nature, 2021)
Apply skills and approaches to your programming to build a real-world application in C# 9 using the latest editions of Visual Studio, C#, and Microsoft .NET. Each chapter opens with an introduction and original application written in C# 9 for you to jump into coding. From there, you are guided through an expected output and taught best practices along the way. Author emphasizes extending and maintaining the same program and he demonstrates examples for different scenarios to make your program more efficient and effective. This book is divided into four parts. The first part starts with a detailed discussion of polymorphism. It then shows you how to make proper use of abstract classes and interfaces, and you will know which technique to use for a specific scenario. Discussions on code comments teach you how to use them effectively, and why you need to be careful with code comments. In the second part you will learn six design principles, including SOLID and DRY principles.